Prospecting glacial ages and paleoclimatic reconstructions northeastward of nevado Coropuna (16° S, 73° W, 6377 m), arid tropical Andes - Úbeda Palenque, José (2018)
This work investigates the timing, paleoclimatic framework and inter-hemispheric teleconnections inferred from the glaciers last maximum extension and the deglaciation onset in the Arid Tropical Andes. A study area was selected to the northeastward of the Nevado Coropuna, the volcano currently covered by the largest tropical glacier on Earth. The current glacier extent, the moraines deposited in the past and paleoglaciers at their maximum extension have been mapped. The present and past Equilibrium Line Altitudes (ELA and paleoELA) have been reconstructed and the chlorine-36 ages have been calculated, for preliminary absolute dating of glacial and volcanic processes. The paleoELA depression, the thermometers installed in the study area and the accumulation data previously published allowed development of paleotemperature and paleoprecipitation models. The Coropuna glaciers were in maximum extension (or glacial standstill) ~20–12 ka ago (and maybe earlier). This last maximum extension was contemporary to the Heinrich 2–1 and Younger Dryas events and the Tauca and Coipasa paleolake transgressions on Bolivian Altiplano. The maximum paleoELA depression (991 m) shows a colder (-6.4 °C) and moister climate with precipitation ×1.2–×2.8 higher than the present. The deglaciation onset in the Arid Tropical Andes was 15–11 ka ago, earlier in the most southern, arid, and low mountains and later in the northernmost, less arid, and higher mountains.